Administrative and Financial Performance Monitoring System in the Medan Mayor's Office - Syawla Andina Auliya; Rahmat Daim Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Organizations or offices need an operation that can do this to manage aspects of work. Financial and administrative aspects are one example, because every organization or office requires reliable capacity to handle various problems within a particular office or agency. This research examines the administrative and financial capacity management system at the Medan Mayor's Office. The aim of this research is a) to understand the system of understanding financial activities in the Medan Mayor's Office, b) to understand the system of understanding the effective management of administrative activities in the Medan Mayor's Office, c). correlation between finance and management in the Medan Mayor's Office. To determine the research methodology, a qualitative descriptive research method was used using three methods, namely observation and documentary interviews. Known to have high performance in management systems. It is important to pay attention to the improvement of the government he leads. because the performance required is accuracy, clarity and punctuality in mastering various aspects as well as in correcting writings related to work in a particular office.